Fundamental Frequencies of Vibration of Footbridges in Portugal: From In Situ Measurements to Numerical Modelling - C. S. Oliveira (Shock and Vibration)
Since 1995, we have been measuring the in situ dynamic characteristics of different types of footbridges built in Portugal (essentially steel and precast reinforced concrete decks) with single spans running from 11 to 110 m long, using expedite exciting and measuring techniques. A database has been created, containing not only the fundamental dynamic characteristics of those structures (transversal, longitudinal, and vertical frequencies) but also their most important geometric and mechanical properties. This database, with 79 structures organized into 5 main typologies, allows the setting of correlations of fundamental frequencies as a negative power function of span lengths L  (L-0.6 to L-1.4). For 63 footbridges of more simple geometry, it was possible to obtain these correlations by typology. A few illustrative cases representing the most common typologies show that linear numerical models can reproduce the in situ measurements with great accuracy, not only matching the frequencies of vibration but also the amplitudes of motion caused by several pedestrian load patterns.